Using AI Assistants in the Creation of an Academic Program of Study (PoS) in CyberAI (Journal of The Colloquium for Information Systems Security Education, 2025)
Artificial Intelligence (AI) is playing an increasingly vital role in cybersecurity. As AI becomes more prevalent, cybersecurity professionals need AI skills, and academic institutions need to provide students with the opportunities to gain them. To meet this demand, the NSA National Centers of Academic Excellence in Cybersecurity (NCAE-C) program, in collaboration with the National Science Foundation (NSF), launched an initiative to outline the AI content cybersecurity academic programs need to teach their students. The initiative aims to build knowledge units (KUs) and recommend a Program of Study (PoS) in Cybersecurity and Artificial Intelligence (Cyber AI). This paper outlines the development of an AI assistant that was used to collaborate on the KU creation process for the CyberAI PoS. We will discuss the methodology behind the integration of the AI assistant, evaluate its contributions, and explore future directions for using AI assistants to develop curricular guidelines for academic programs.
Keywords: CyberAI; AI Assistants; Curricular Guidelines; Cybersecurity; Artificial Intelligence